Under pressure from Slovak nationalists: The status and political activity of the Rusins in Slovakia 1939-1945 - Pekár, Martin (Русин)
The article examines the position of the Rusin minority in Slovakia during 1939-1945 and the political activities of the minority's representatives in the conditions of the then authoritarian regime of the Hlinka Slovak People's Party. The Rusin minority was an integral part of the Slovak population, but suffered from economic, social, and cultural backwardness. Nevertheless, its representatives had the ambition to be an active part of political life in the conditions that the legislation of the time allowed them. However, they constantly encountered the disinterest and distrust of the regime. Based on primary sources and published works, the article analyses and interprets the specific political activities of the Rusin minority, as well as the attitudes of the regime's representatives towards the minority. It points to the fact that the Rusin minority found itself under the pressure of Slovak nationalism, because of which the possibilities of political life were limited, without the possibility of founding its own political party. The activities of the representatives of the minority were fully under the control of the regime.